A Late Pleistocene human humerus from Rusinga Island, Lake Victoria, Kenya. Issue 146 (September 2020) - Pearson, Osbjorn M.; Hill, Ethan C.; Peppe, Daniel J.; Van Plantinga, Alex; Blegen, Nick; Faith, J. Tyler; Tryon, Christian A.
Abstract: In 2010, a hominin right humerus fragment (KNM-RU 58330) was surface collected in a small gully at Nyamita North in the Late Pleistocene Wasiriya Beds of Rusinga Island, Kenya. A combination of stratigraphic and geochronological evidence suggests the specimen is likely between ∼49 and 36 ka in age. The associated fauna is diverse and dominated by semiarid grassland taxa. The small sample of associated Middle Stone Age artifacts includes Levallois flakes, cores, and retouched points. The 139 mm humeral fragment preserves the shaft from distal to the lesser tubercle to 14 mm below the distal end of the weakly projecting deltoid tuberosity. Key morphological features include a narrow and weakly marked pectoralis major insertion and a distinctive medial bend in the diaphysis at the deltoid insertion. This bend is unusual among recent human humeri but occurs in a few Late Pleistocene humeri. The dimensions of the distal end of the fragment predict a length of 317.9 ± 16.4 mm based on recent samples of African ancestry. A novel method of predicting humeral length from the distance between the middle of the pectoralis major and the bottom of the deltoid insertion predicts a length of 317.3 mm ± 17.6 mm. Cross-sectional geometry at the midshaft shows a relatively high percentage of cortical bone and a moderate degree of flattening of the shaft. The Nyamita humerus is anatomically modern in its morphology and adds to the small sample of hominins from the Late Pleistocene associated with Middle Stone Age artifacts known from East Africa. It may sample a population closely related to the people of the out-of-Africa migration.